Dios en la literatura contemporánea: un viaje hacia la luz - Palenzuela Oca, Francisco José (Revista de espiritualidad, 2022)
After a brief presentation of the project "God in Contemporary Literature", some ideas about the relationship between symbol and literature are discussed, as well as the symbolism of light. Finally, reference is made to three literary texts related to this topic: The Razor's Edge, a novel by W. Somerset Maugham; The Blue Bird, a play by M. Maeterlinck, and "Knowledge", a poem by H. Hesse.